Desain Prototype Mobile Classes Dengan Menggunakan Model Lean UX - Mandey, Jessica Fransisca; Muawwal, Ahyar; Renny, Renny (STMIK KHARISMA Makassar, 2024)
Classes is a website-based information system application that contains such as student academic information that can be accessed by student anytime and anywhere. With Classes, it is hoped this website can help students find out academic information about each student such as student profile, attendance, teacher profile, list of grades, materials orteaching materials for each subject. Classes has a weakness, that it is still in the form of a website and not yet based on a mobile device or application, so using Classes is still less effective and efficient for users who expect a mobile version of Classes along with the development of technology. By looking at this problem, the author provides a solution by applying the Lean UX method in designing prototype for Classes mobile devices which can then be developed further so as to help users who expect a mobile display. In creating a prototype for the Classes mobile device, the author used supporting editing software, namely Figma, so that the user interface of this mobile device can present information in a friendly, interesting and informative way for Classes users according to aech user’s needs. And with this research, the author hopes that Classes can become the main access medium for all information related to student’s and teacher’s academics, and the appearance of the Classes mobile device will become more attractive in terms of appropriate User Interface (UI) and User Experience (UX) with user needs